(untitled) (ELEKTRIKA- Journal of Electrical Engineering, 2021)
To date, the deposition of AlGaN thin film using the co-sputtering technique at room temperature has not been reported yet. The use of AlGaN for electronic devices has been widely known because of its ultra-wide bandgap. However, to deposit the AlGaN thin film and achieved high quality of AlGaN films, higher temperature or extra time deposition are needed, which is not compatible with industrial fabrication process. Here, a co-sputtering technique between two power supplies of magnetron sputtering (which are RF and HiPIMS) is introduced to deposit the AlGaN thin films. The AlGaN thin films were deposited at various RF power to study their effect on structural properties and morphology of the thin films. AlGaN films were sputtered simultaneously on silicon (111) substrate for short time and at room temperature using GaN and Al target. Then, the films were characterized by X-ray diffraction (XRD), atomic force microscopy (AFM), and surface profiler to study their properties. XRD shows the GaN (101) and (013) plane for the AlGaN deposited at RF power of 30 W. Also there only GaN (101) for the AlGaN with 50 W RF power. Yet, the 70 W RF power shows the amorphous structure of AlGaN. The roughness and the grain size of AlGaN film from AFM analysis showed the trend of decreasing and increasing respectively. The roughness of the AlGaN films with 30 W power was 0.82 nm, 0.85 nm for 50 W, and 0.46 nm for 70 W RF power. The grain size of the AlGaN films was 30.06 nm, 32.10 nm, and 37.65 nm for RF power of 30 W, 50 W, and 70 W respectively. The profilometer found that the thickness of the AlGaN films was decreasing with increasing of RF power. This paper can demonstrate a successful co-sputtering technique of AlGaN. Despite AlGaN crystal structure was not able to found out in the XRD analysis, the effect of RF power has been studied to give significant effects on AlGaN thin film deposition.